Study on liver histopathology of chronic HBV infected patients with different normal ALT values - Zeng, Zhan; Hao, Hongxiao; Bi, Xiaoyue; Lin, Yanjie; Yang, Liu; Wang, Shiyu; Shen, Ge; Chang, Min; Jiang, Tingting; Deng, Wen; Lu, Huihui; Sun, Fangfang; et al. (Frontiers in Immunology, 2022)
Aims Comparison of liver histopathological findings to explore the occurrence of liver inflammation in patients with chronic hepatitis B (CHB) under different alanine aminotransferase (ALT) normal values. Methods The patients who were diagnosed as chronic hepatitis B virus (HBV) infection by liver histopathology at the Department of Pathology, Beijing Ditan Hospital due to clinical difficulty in defining the degree of liver inflammation or fibrosis were retrospectively enrolled from May 2008 to November 2020. Study of the incidence of significant hepatic histopathology in enrolled patients according to different ALT normal values. Using logistic regression to investigate the relevant factors of significant hepatic histopathology. Results A total of 1474 patients were enrolled, 56.20% of the patients were male, and the overall patients’ age was 36.80 ± 10.60 years. 39.00% of patients had liver inflammation grade G > 1, 34.70% liver fibrosis stage S > 1, and 48.17% patients had significant hepatic histopathology (G > 1 and/or S > 1). Among patients with normal ALT values, 36.40% and 40.40% had significant hepatic histopathology by American Association for the Study of Liver Diseases (AASLD) criteria and Chinese guideline criteria, respectively, but the difference was not statistically significant (χ2 =3.38, P =0.066). In contrast, among patients with abnormal ALT values, 58.90% and 62.20% of patients had significant hepatic histopathology by AASLD criteria and Chinese guideline criteria, respectively, with no significant difference (χ2 =2.28, P =0.131). ALT (P <0.001, OR=1.019), hepatitis B surface antigen (HBsAg) (P <0.001, OR=0.665) and hepatitis B e antigen (HBeAg) status (P <0.001, OR=2.238) were relevant factors in the occurrence of significant hepatic histopathology. ALT was positively corelated with grade of inflammation G (r =0.194, P <0.001) and negatively correlated with liver fibrosis stage S (r =-0.066, P =0.021). Conclusions Our study found no statistically significant differences in the presence of significant hepatic histopathology under the two ALT criteria. ALT, HBsAg and HBeAg status were related to the occurrence of significant hepatic histopathology.